An Evaluation Of The Industrial Job Training At Vocational High School - Andi Faisal Naharuddin; Sudji Munadi (Journal of Educational Science and Technology (EST), 2018)
The research aims to evaluate industrial job training in terms of: context, input, process, and product.This research model used the CIPP model with a quantitative descriptive approach. Data was collected on research respondents from vice principal for industrial relations, 18 teachers, 18 BS/BI from Buol Regency, Tolitoli Regency, Gorontalo Province and 110 students using questionnaire, observations, interviews, and documentations. The results of the study show in terms of: (1) context where the results of data analysis are in the appropriate category, but the achievement of the objectives of apprenticeship is less than optimal, namely providing increased competence to students to become quality workforce and having professional expertise. Planning, drafting, not paying attention to the condition of the school's ability in terms of learning, in synchronizing competencies that do not involve BS / IS elements, and the development of cooperation between industrial and labor through the MoU have not been well realized; (2) input where the results of data analysis are in a very suitable category, but the lack of industry in designing debriefing is an obstacle. Still needing the readiness of participants in terms of competencies where the obstacles faced are more about mastery of competence and lack of work readiness so that maximizing the time and material of debriefing is very necessary; (3) the process where the results of data analysis are in the appropriate category, but the lack of maximum role and responsibility of the supervisor causes communication of the development of students' competencies less monitored; (4) product where the results of data analysis are in a very appropriate category, it is shown by the changes that occur by students in terms of attitudes, responsibilities and increased competence.